The Predation Strategy of Myxococcus xanthus - Thiery, Susanne; Kaimer, Christine (Frontiers in Microbiology, 2020)
Myxobacteria are ubiquitous in soil environments. They display a complex life cycle: vegetatively growing cells coordinate their motility to form multicellular swarms, which upon starvation aggregate into large fruiting bodies where cells differentiate into spores. In addition to growing as saprophytes, Myxobacteria are predators that actively kill bacteria of other species to consume their biomass. In this review we summarize research on the predation behavior of the model myxobacterium Myxococcus xanthus, which can access nutrients from a broad spectrum of microorganisms. M. xanthus displays an epibiotic predation strategy, i.e. it induces prey lysis from the outside and feeds on the released biomass. This predatory behavior encompasses various processes: Gliding motility and induced cell reversals allow M. xanthus to encounter prey and to remain within the area to sweep up its biomass, which causes the characteristic "rippling" of preying populations. Antibiotics and secreted bacteriolytic enzymes appear to be important predation factors, which are possibly targeted to prey cells with the aid of outer membrane vesicles. However, certain bacteria protect themselves from M. xanthus predation by forming mechanical barriers, such as biofilms and mucoid colonies, or by secreting antibiotics. Further understanding the molecular mechanisms that mediate myxobacterial predation, will offer fascinating insight into the reciprocal relationships of bacteria in complex communities, and might spur application-oriented research on the development of novel antibacterial strategies.